Cassidinae of Panama, part 1 (Coleoptera: Chrysomelidae) - Sekerka, Lukáš (Jihočeská univerzita, 2009)
The study deals with taxonomy of Cassidinae of Panama and is based on extensive new material compared with the type specimens in various museums. Totally is listed 178 species of which 33 and two genera are described as new to science.
Cassidinae of Panama, part 1 (Coleoptera: Chrysomelidae)
Keywords: entomology; taxonomy; biogeography; faunistics; Panama; new genus; new species; new synonymy; lectotype designation; host plant; entomology; taxonomy; biogeography; faunistics; Panama; new genus; new species; new synonymy; lectotype designation; host plant